(untitled) (Research, Society and Development, 2021)
Objective: To assess factors associated with the average number of dental caries in pregnant women. Method: Basic research design: This cross-sectional study was performed between January 2017 and December 2018 in Santa Maria, Brazil. Clinical setting and participants: Multistage random sampling resulted in the recruitment of 256 pregnant women from public health centers across the city. Clinical exams and semi-structured questionnaires including demographic, socioeconomic and behavioral questions were performed by trained interviewers. Main outcome measure: The experience of dental caries was evaluated through the mean value of the Decay, Missing, and Filled Surface Index (DMFS) by 4 trained and calibrated examiners. Multilevel Poisson regression models were used to evaluate the influence of different variables on the average number of dental caries. Rate ratio (RR) and respective 95% confidence intervals were calculated (CI 95%). Results: The prevalence of untreated dental caries was 62.7% in the sample, while the mean DMFS index was 10.27 (± 10.92). Women who smoked during pregnancy had a higher mean DMFS (RR 1.41; 95% CI 1.25-1.57). Furthermore, pregnant women who had poor self-ratings of oral health had a higher average DMFS (RR 1.21; 95% CI 1.10-1.32). Conclusions: The results showed that older age, ethnicity, fewer years in education and the presence of dental plaque resulted in higher means of DMFS.